Depcition of Vayu with four arms - Temples of India Project Team (Jio Institute, 2024)
Vayu (one of the deities of the cardinal directions) is depicted with four arms, each holding his respective attributes. Crowned, Vayu is accompanied by his vahana (mount), the antelope, positioned at his feet. In his upper hands, he holds a dhvaja (flag), while his lower left-hand grasps a kamandalu (water pot). His lower right-hand holds a rosary and also makes a varada hasta (boon-giving gesture).